The Risk Factors Affecting Survival in Colorectal Cancer in Taiwan - Chao-Hsien LEE; Shu-Chen CHENG; Hong-Yi TUNG; Shih-Chang CHANG; Ching-Yun CHING; Shu-Fen WU (Tehran University of Medical Sciences, 2018)
Background: Colorectal cancer is one of the most common malignancies in developed countries. The incidence of colorectal cancer (CRC) in Taiwan is rising. We aimed to determine the five-yr survival rate of patients diagnosed with CRC and determine factors affecting survival. Methods: All patients were identified from the Taiwan Cancer Data Base of the Medical Center Hospital in North Taiwan from 2007 to 2013. Data were collected using medical records and the cancer database. In all, 869 patients with CRC were included. Survival analysis was performed using Kaplan-Meier curves, and differences between the curves were analyzed using the log-rank test. Cox proportional hazards regression models were used to analyze survival by each variable. Results: The five-yr survival rate and the mean survival time after cancer diagnosis were 68.7% and 71.27±1.27 months. Perineural nerve invasion, distant metastasis, age, pathological differentiation grade, obstruction and regional lymph node metastasis were found to be independent predictors of the survival and prognosis of patients with CRC. Conclusion: Perineural nerve invasion was an important factor related to the survival of CRC patients. Thus, the earlier detection of CRC might help improve survival.